Modeling of Modern International Conflicts - Patiychuk, Victor; Патійчук, Віктор (Східноєвропейський національний університет ім. Лесі Українки, 2017)
The main theoretical positions concerning the possibilities of using the modeling of foreign political processes, including international conflicts, in practice are generalized. The specifics of the use of conflict modeling in contemporary international conflict research is considered. The main forms, content and tasks of modern international conflicts modeling are defined. Some methods of international relations modeling and complex manifestations of the foreign policy situation are investigated. Practical aspects of the possibilities of contemporary international conflicts modeling are analyzed. Concrete methods of international conflicts modeling are described and their practical content is disclosed. The main disadvantages of mathematical modeling in the study of modern international conflicts and foreign policy processes are indicated. Expediency of using modeling methods in research and forecasting of problem international situations and international conflicts in practice is accented. The author points to the potential prospects for the use of modeling techniques in further foreign policy analysis of contemporary international relations. Узагальнено основні теоретичні положення щодо можливостей застосування моделювання зовнішньополітичних процесів, у тому числі й міжнародних конфліктів, на практиці. Розглянуто специфіку використання методів моделювання в сучасних міжнародних конфліктологічних дослідженнях. Визначено основні форми та зміст і завдання моделювання сучасних міжнародних конфліктів. Досліджено деякі методики моделювання міжнародних відносин та складних проявів зовнішньополітичної ситуації. Проаналізовано практичні аспекти щодо можливостей моделювання сучасних міжнародних конфліктів. Описано конкретні методики моделювання міжнародних конфліктів і розкрито їх практичний зміст. Показано основні недоліки математичного моделювання у вивченні сучасних міжнародних конфліктів та зовнішньополітичних процесів. Акцентовано на доцільності використання методів моделювання в дослідженні й прогнозуванні розвитку проблемних міжнародних ситуацій та міжнародних конфліктів на практиці та вказано на потенційні перспективи використання методик моделювання в подальшому зовнішньополітичному аналізі сучасних міжнародних відносин.
Моделювання сучасних міжнародних конфліктів
Keywords: modeling; international conflicts; modeling process; modeling situation; models of international conflicts; international relations; foreign policy environment; моделювання; міжнародні конфлікти; процес моделювання; модельована ситуація; моделі міжнародних конфліктів; міжнародні відносини; зовнішньополітичне середовище